(untitled) (IUBAT Review, 2025)
Sandwip, an offshore island, is highly dynamic due to its geographical location and is experiencing significant morphological changes. To evaluate the effects of shoreline changes brought on by accretion and erosion on communities, it is crucial to comprehend these changes. This study analyzes shoreline and land use dynamics of Sandwip Island from 1994 to 2024 using Landsat satellite imagery. For this purpose, Landsat images from 1994 to 2024 were analyzed in this study. Shoreline digitization and Normalized Difference Water Index (NDWI) analysis were conducted to accurately delineate the water-land interface and assess the rates of coastal erosion and accretion, and a supervised classification technique was used for Land Use and Land Cover (LULC) classification from 1994 to 2024. The findings revealed that accretion was the dominant process from 1994 to 2004, while erosion became dominant from 2004 to 2014 and continued through 2024. Over the past 30 years, erosion prevailed overall, with the southwestern side of the island particularly vulnerable to erosion and the northeastern side to accretion. The total land area of Sandwip steadily declined from 1994 to 2024 (approximately 33.266 sq. km). Land Use and Land Cover (LULC) analysis showed a significant conversion of barren land to water bodies between 1994 and 2024. The implications of this study are vital for coastal management, as it provides data to guide sustainable development. IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 206-222